EFFECT OF UREA WITH UREASE INHIBITOR ON THE GROWTH OF COFFEE SEEDLINGS (Coffea arabica L.) - Alvarenga Garcia, André Luiz; Padilha, Lilian; Wander Rafael Garcia, Antônio; Nazareno Guimarães Mendes, Antônio; Siqueira de Carvalho, Carlos Henrique (Coffee Science - ISSN 1984-3909, 2011)
The urea-based fertilizers may suffer significant losses of nitrogen to the atmosphere. This is due to the transformation of urea to ammonia in the presence of urease produced by soil microorganisms. The aim of this study was to evaluate the effect of the combination of urea with urease inhibitor NBPT [N-(n-butyl) thiophosphoric triamide, nitrogen absorption and development of coffee seedlings. The experiment was conducted in a greenhouse in a factorial design. We evaluated three doses of N-urea in the presence and absence of NBPT divided into two installments. Were also considered two periods of water supply: before and after fertilization. Three additional treatments were included: control without nitrogen, 7.2 g of urea-N (in a single application) with and without NBPT. Four months after the second installment we evaluated the total production of dry matter (DM) and nitrogen absorbed. The use of NBPT favored the increase of DM and nitrogen absorbed proportionally to the dose of N applied. The supply of water before or after covering the fertilizer did not influence any features. The control sample behaved less than all other treatments. It was observed that application of 7.2 g N-urea performed in a single dose caused plant mortality on the second day after application of fertilizer without NBPT, and on the sixth day when urea was associated with an inhibitor. Potted Coffee seedlings fertilized with urea-NBPT exploit the N available more efficiently. They have an 18% gain in dry matter production and a 32% increase in the N absorbed.